REVIEWING TEACHER PERFORMANCE: A LESSON FROM JUNIOR HIGH SCHOOL TEACHERS - Imron; Lilik Fatkhu Diniyah (MANAGERIA: Jurnal Manajemen Pendidikan Islam, 2021)
This study aims to determine how principal leadership influences teacher performance through organizational commitment and Organizational Citizenship Behavior in SMP Negeri (Junior High School) teachers in Magelang Regency. This study used a quantitative approach with a population of all SMP Negeri teachers in Magelang regency. The sampling technique used is Probability Sampling with Simple Random Sampling, while the data collection technique used a questionnaire. Data analysis used: (1) descriptive statistics; (2) Multiple Regression; and (3) Path Analysis. The results showed that the principal's leadership significantly affected SMP Negeri's performance in Magelang Regency through organizational commitment and OCB. The better the principal's leadership, the better the teacher's account will be.